The Bohemian South : Creating Countercultures, from Poe to Punk - Freeman, Lindsey A.; Bingham, Shawn Chandler, 1976- (Book collections on Project MUSE., 2017)
"This ... collection uses bohemia as a novel lens for reconsidering more traditional views of the South. Exploring wide-ranging locales, such as Athens, Austin, Black Mountain College, Knoxville, Memphis, New Orleans, and North Carolina's Research Triangle, each essay challenges popular interpretations of the South, while highlighting important bohemian sub- and countercultures. The bohemian South provides [a] perspective in the new South as an epicenter for progress, innovation, and experimentation"--